Science and/in Literature: A Californian Perspective - Kopecký, Petr (American & British Studies Annual, 2020)
This essay explores the intersection of science and literary expression in Californian literature. It aims to analyze a current in said literature characterized by the convergence of literature and science. In so doing, the essay probes four thematic layers that play a prominent role in Californian environmental literature: 1) ecology and Darwinian science, 2) the holistic approach to science, 3) the geological imagination, 4) and imagined worlds in ecological science fiction. Investigating literary works spanning from the late 19th century to the early 21st century, the essay addresses authors such as John Muir, Mary Austin, Robinson Jeffers and John Steinbeck, each of whom incorporated science into their imaginative writing. In addition to these quintessential Californian authors, the essay also probes texts by writers who experienced the dramatic degradation of the California environment in the 1960s and was further aggravated by climate change at the turn of the century. These writers include Gary Snyder, Ernest Callenbach, Ursula Le Guin and Kim Stanley Robinson. The essay identifies a distinctive and coherent thread that runs through the texts under scrutiny, one characterized by a critical and skeptical attitude to fragmented science and its ambition to control rather than apprehend the natural world. In contrast, the writers draw from the inclusive and holistic approach applied by Charles Darwin.